(untitled) (Fiep Bulletin - online, 2017)
Performance is based on increasing physical abilities, being observed from year to year, the more the adolescentimproves strength, stamina, reaction time, speed of movement, coordination and so on, we can expect to observe better andbetter levels of performance. Physical Education can contribute to the teaching-learning process, it is necessary to know thecharacteristics of the students in their potentialities, limitations and needs in their development. "Providing learning opportunitiesand development of fundamental motor skills is of utmost importance for children’s development. The definition of motordevelopment allows professionals to identify the factors that make movement limited, making it possible to decide which skill and/ or motor criteria Which should be emphasized in the program, the practice time for each skill and the performance goals of thechild. Agility is one of the most important motor performance variables in physical education, which directly influences strength,speed, flexibility and coordination , Developing in the student the mastery of the body and the confidence in itself. Being this usedin almost all the batteries of tests of physical aptitude. In general sports such as basketball, futsal, tennis and day to day agilityplays a fundamental role in motor development, the methodology was the tests: Agility (Test of Square), were submitted to theprogram 38 adolescents from 13 to 16 in the period of 10 months, twice a week with approximately one hour of training in severalmodalities. In the comparison of the pretest and post test results, we verified that the activities developed influenced the flexibilityof the adolescents, based on the means, but according to p = 0.574, we verified that the difference was not significant. Theconclusion tells us that we developed a periodization where the results showed the efficiency in the agility, because we were ableto develop or even maintain a pattern, but without significant difference in evaluating the results obtained before the interventionwith those obtained after.